Chloride-bicarbonate exchange in human red cells measured using a stopped flow apparatus. - Lambert, A (1980)
1. A new stopped-flow apparatus has been used to measure the exchange of intracellular chloride and extracellular bicarbonate across the human erythrocyte membrane at 37 degrees C. 2. The concentration dependence of the activation of the anion exchange system by extracellular bicarbonate was consistent with the existence of a saturable membrane-carrier. Analysis of the results assuming Michaelis--Menten kinetics indicated a Vmax for chloride--bicarbonate exchange of 73 . 4 +/- 14 . 4 mol. (3 x 10(13) cells.min)-1 and Km for bicarbonate of 11 . 1 +/- 2 . 8 mM at 37 degrees C (pH 7 . 1). 3. Correction of the directly computed values of Vmax for incomplete saturation of the carrier by intracellular chloride and the inhibitory effects of intracellular bicarbonate and extracellular chloride gave a Vmax of 157 +/- 43 . 8 mol (3 x 10(13) cells.min)-1 and a Km of 15 . 5 +/- 5 . 2 mM-bicarbonate at 37 degrees C. 4. Comparison of Vmax obtained at 37 and 10 degrees C indicates that the activation energy for chloride--bicarbonate exchange in this temperature range is 18 . 7 --19 . 6 kcal.mol-1 depending on whether corrected or uncorrected values are used. 5. Extracellular furosemide inhibited chloride--bicarbonate exchange with a KI of 0 . 12 microM assuming competition between furosemide and bicarbonate and 0 . 17 microM assuming non-competitive inhibition. 6. Extracellular chloride also inhibited chloride--bicarbonate exchange but the kinetics of inhibition were complex.